2016
DOI: 10.1111/jcal.12131
|View full text |Cite
|
Sign up to set email alerts
|

Understanding MOOC students: motivations and behaviours indicative of MOOC completion

Abstract: Massive open online courses (MOOCs) continue to appear across the higher education landscape, originating from many institutions in the USA and around the world. MOOCs typically have low completion rates, at least when compared with traditional courses, as this course delivery model is very different from traditional, fee-based models, such as college courses. This research examined MOOC student demographic data, intended behaviours and course interactions to better understand variables that are indicative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(135 citation statements)
references
References 30 publications
8
119
1
7
Order By: Relevance
“…Often, researchers distinguish between completion and drop-off, where completion is defined as students who submitted the final exam (Ramesh et al, 2014), students who showed behaviour in the last week (Sinha et al, 2014), or students who earned a normal or "with distinction" certificate (Allione & Stein, 2016;Jiang et al, 2014;Pursel, Zhang, Jablokow, Choi, & Velegol, 2016) and by selfreports of (partially) completion (Adamopoulos, 2013). Often, researchers distinguish between completion and drop-off, where completion is defined as students who submitted the final exam (Ramesh et al, 2014), students who showed behaviour in the last week (Sinha et al, 2014), or students who earned a normal or "with distinction" certificate (Allione & Stein, 2016;Jiang et al, 2014;Pursel, Zhang, Jablokow, Choi, & Velegol, 2016) and by selfreports of (partially) completion (Adamopoulos, 2013).…”
Section: Defining Student Performance In Moocsmentioning
confidence: 99%
“…Often, researchers distinguish between completion and drop-off, where completion is defined as students who submitted the final exam (Ramesh et al, 2014), students who showed behaviour in the last week (Sinha et al, 2014), or students who earned a normal or "with distinction" certificate (Allione & Stein, 2016;Jiang et al, 2014;Pursel, Zhang, Jablokow, Choi, & Velegol, 2016) and by selfreports of (partially) completion (Adamopoulos, 2013). Often, researchers distinguish between completion and drop-off, where completion is defined as students who submitted the final exam (Ramesh et al, 2014), students who showed behaviour in the last week (Sinha et al, 2014), or students who earned a normal or "with distinction" certificate (Allione & Stein, 2016;Jiang et al, 2014;Pursel, Zhang, Jablokow, Choi, & Velegol, 2016) and by selfreports of (partially) completion (Adamopoulos, 2013).…”
Section: Defining Student Performance In Moocsmentioning
confidence: 99%
“…In MOOCs, completion rates may differ by students' level of prior educational attainment (Pursel, Zhang, Jablokow, Choi, & Velegol, 2016), but this is not always the case (Goldberg et al, 2015). Currently, there is a great deal of interest in identifying quantifiable predictors of student retention and engagement as a means to intervene early in both traditional and online educational settings.…”
Section: Optimizing Engagement and Learning In Online Coursesmentioning
confidence: 99%
“…Numerous studies have demonstrated a relationship between prior variables, including student demographics, and learning in traditional and online courses (Casillas et al, 2012;Geiser & Santelices, 2007;Pursel et al, 2016). We used ordinal logistic regression to test whether participants' self-reported background information (gender, education, biology background, experience with online courses, and time spent on various educational activities) was predictive of post-test scores.…”
Section: Predicting Post-test Scoresmentioning
confidence: 99%
“…And do a comparative study of classroom learning and online learning. Bart Pursel et al (2016) [9] studied MOOC learners' demographic data, learning behaviors and course interaction data. Stich (2017) [10] analyzed the MOOC in the United States and found that the platform blindly pursued the number of courses but neglected the service to learners.…”
Section: The Knowledge System Of the Course Limits The Freedom Of Leamentioning
confidence: 99%